Dynamic molecular analysis and clinical correlates of tumor evolution within a phase II trial of panitumumab-based therapy in metastatic colorectal cancer. (4th September 2017) - Siena, S; Sartore-Bianchi, A; Garcia-Carbonero, R; Karthaus, M; Smith, D; Tabernero, J; Van Cutsem, E; Guan, X; Boedigheimer, M; Ang, A; Twomey, B; Bach, B A; et al.
Abstract: Background: Mutations in rat sarcoma ( RAS) genes may be a mechanism of secondary resistance in epidermal growth factor receptor inhibitor-treated patients. Tumor-tissue biopsy testing has been the standard for evaluating mutational status; however, plasma testing of cell-free DNA has been shown to be a more sensitive method for detecting clonal evolution. Materials and methods: Archival pre- and post-treatment tumor biopsy samples from a phase II study of panitumumab in combination with irinotecan in patients with metastatic colorectal cancer (mCRC) that also collected plasma samples before, during, and after treatment were analyzed for emergence of mutations during/post-treatment by next-generation sequencing and BEAMing. Results: The rate of emergence of tumor tissue RAS mutations was 9.5% by next-generation sequencing ( n = 21) and 6.3% by BEAMing ( n = 16). Plasma testing of cell-free DNA by BEAMing revealed a mutant RAS emergence rate of 36.7% ( n = 39). Exploratory outcomes analysis of plasma samples indicated that patients who had emergent RAS mutations at progression had similar median progression-free survival to those patients who remained wild-type at progression. Serial analysis of plasma samples showed that the first detected emergence of RAS mutations preceded progression by a median of 3.6 months (range, −0.3 to 7.5 months) and that there did not appear to be a mutant RAS allele frequency threshold that could predict near-term outcomes. Conclusions: This first prospective analysis in mCRC showed that serial plasma biopsies are more inclusive than tissue biopsies for evaluating global tumor heterogeneity; however, the clinical utility of plasma testing in mCRC remains to be further explored. ClinicalTrials.gov Identifier: NCT00891930